Canada: Peary Arctic Club, 1898-1902, Cape D'Urville - Peary, Robert E. (Robert Edwin), 1856-1920 (1898)
Winter quarters at C[ape] D'Urville (1898-1899) http://www.matthewhenson.com/1909NPtrip/1910b.html